2012
DOI: 10.2151/sola.2012-003
|View full text |Cite
|
Sign up to set email alerts
|

Development Processes of Baiu Frontal Depressions

Abstract: This work investigates development processes of Baiu frontal depressions (BFDs) using a reanalysis data set in June and July from 2000 to 2007. On the basis of the deepening magnitude, 140 BFDs detected in the analysis period are categorized into developed and non-developed BFDs. Developed BFDs are further classified into W-BFDs and E-BFDs; W-BFDs (E-BFDs) peak in the region west (east) of 140°E.A composite analysis and many case studies reveal that the vertical coupling between lower-and upper-level disturban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 13 publications
3
13
0
Order By: Relevance
“…A large number of BFDs are accompanied by upper-level troughs and have structures tilted westward with height (e.g., Akiyama 1984;1990a, b;Tagami et al 2007;Tochimoto and Kawano 2012;hereafter TK12). These structures are consistent with baroclinic instability waves in mid-latitudes (e.g., Charney 1947;Eady 1949).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of BFDs are accompanied by upper-level troughs and have structures tilted westward with height (e.g., Akiyama 1984;1990a, b;Tagami et al 2007;Tochimoto and Kawano 2012;hereafter TK12). These structures are consistent with baroclinic instability waves in mid-latitudes (e.g., Charney 1947;Eady 1949).…”
Section: Introductionmentioning
confidence: 99%
“…These differences must influence the development of BFDs. Recently, Tochimoto and Kawano (2012) categorized BFDs into two groups on the basis of the region-BFDs that developed in the western (west of 140°E) and eastern (east of 140°E) parts of the Baiu frontal zone were referred to as W-BFDs and E-BFDs, respectively. They performed composite analyses and a number of case studies investigating the development processes by using the piecewise PV inversion technique developed by Davis and Emanuel (1991).…”
Section: Introductionmentioning
confidence: 99%
“…Moisture is provided from the tropics along the western and northern rim of the North Pacific high, and in early summer the Meiyu-Baiu rainband is formed. Extensive studies of the meso-scale disturbances along the Meiyu-Baiu frontal zone have covered many aspects, from their climatology to their dynamics (Ninomiya and Akiyama 1992;Ninomiya and Shibagaki 2007, and the references therein), which includes their forcing by means of the piecewise potential vorticity inversion (e.g., Chen et al 2003;Tochimoto and Kawano 2012). However, much fewer studies have examined the dynamics of the synoptic Meiyu-Baiu variability (e.g., Akiyama 1990;Chang et al 1998), and there are even fewer synoptic studies of mid-summer precipitation (e.g., Chen et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Matsumoto et al (1970) suggested that the kinetic energy of an intermediate-scale disturbance (frontal cyclone over the Baiu front) was transformed from the kinetic energy of convective motion. Tochimoto and Kawano (2012) found through a composite analysis and case studies that latent heating played an important role in the development of western Baiu frontal depressions. Recently, Jung and Lee (2013) found that an ML that brought heavy rainfall to the Seoul area was initiated by mesoscale convective systems (MCSs) along the Changma front over the Yellow Sea.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have noted the importance of convective forcing for the development of monsoon fronts and associated disturbances (e.g., Matsumoto et al, 1970;Wang and Orlanski, 1987;Tochimoto and Kawano, 2012;Jung and Lee, 2013). Wang and Orlanski (1987) found through a numerical study that, without latent heating, dynamic instability and/or forcing of the large-scale flow interaction with the Tibetan Plateau was not sufficient to generate a heavy-rain vortex originating on the lee side of the Tibetan Plateau.…”
Section: Introductionmentioning
confidence: 99%